Tongue Hygiene and Its Significance in the Control of Halitosis - Lawande, Sandeep Anant; Lawande, Gayatri Sandeep (Journal of Orofacial Research, 2013)
Halitosis or oral malodor refers to the foul smell emanating from the oral cavity. This unpleasant condition frequently poses a problem in social communication and is also a common psychological concern. In the majority of cases, the origin of halitosis is related to an oral cause. Tongue coating is one of the important etiological factors of halitosis. Tongue is a potential reservoir of microorganisms which are responsible for the production of malodorous volatile sulfur compounds. A strong correlation has been established between tongue coating and halitosis. Tongue cleaning, on a regular basis, controls halitosis by removal of tongue coating and/or by reducing putrefaction by bacteria. Different approaches, mechanical as well as chemical, have been employed in the prevention and treatment of halitosis derived from the tongue coating. This article highlights the potential need for concentrating on tongue hygiene as a partof daily routine.